Deterministic Modeling of HIV–Malaria Co-Infection and Sensitivity Analysis in Papua - Vina Lusiana; Diva Hardiestya Fanny; Muhammad Syazali (Mathematics Department, Maulana Malik Ibrahim State Islamic University of Malang, 2026)
HIV and malaria co-infection poses a significant public health challenge in Papua, Indonesia, where high HIV prevalence overlaps with persistent malaria endemicity. Their biological interaction worsens clinical outcomes and complicates transmission. This study develops a deterministic mathematical model using nonlinear differential equations to describe HIV–malaria co-infection dynamics, tailored to Papua's epidemiology. The model includes coupled human and vector compartments and is analyzed through disease-free and endemic equilibria. The basic reproduction number R_0 is derived using the next-generation matrix method and its sensitivity is assessed using normalized forward sensitivity indices to identify key parameters affecting transmission. The results show that the HIV transmission rate (β_H), the mosquito bite rate (b_M), and the malaria transmission from humans to mosquitoes (β_V) increase the most strongly R_0, while the progression of HIV to AIDS (α_1), malaria-induced mortality (δ_M), and vector mortality (μ_V) reduce it. Numerical simulations based on realistic initial conditions for Papua indicate that the system reaches a stable equilibrium when interventions target the most sensitive parameters. These findings provide a mathematical foundation for integrated control strategies, emphasizing reduced human–vector contact, suppression of HIV transmission, and effective vector control. The model enriches biomathematics research on co-infection dynamics and supports evidence-based policymaking for managing dual epidemics in regions like Papua.